Maya after War : Conflict, Power, and Politics in Guatemala - Burrell, Jennifer L. (Book collections on Project MUSE., 2013)
Guatemala's thirty-six-year civil war culminated in peace accords in 1996, but the postwar transition has been marked by continued violence, including lynchings and the rise of gangs, as well as massive wage-labor exodus to the United States. For the Mam Maya municipality of Todos Santos Cuchumatan, inhabited by a predominantly indigenous peasant population, the aftermath of war and genocide resonates with a long-standing tension between state techniques of governance and ancient community-level power structures that incorporated concepts of kinship, gender, and generation. Showing the ways in which these complex histories are interlinked with wartime and enduring family/class conflicts, this book provides a nuanced account of a unique transitional postwar situation, including the complex influence of neoliberal intervention. Drawing on ethnographic field research over a twenty-year period, the author explores the after-war period in a locale where community struggles span culture, identity, and history. Investigating a range of tensions from the local to the international, the author employs unique methodologies, including mapmaking, history workshops, and an informal translation of a historic ethnography, to analyze the role of conflict in animating what matters to Todosanteros in their everyday lives and how the residents negotiate power. Examining the community-based divisions alongside national postwar contexts, this book considers the aura of hope that surrounded the signing of the peace accords, and the subsequent doubt and waiting that have fueled unrest, encompassing generational conflicts. This study is an analysis of the multifaceted forces at work in the quest for peace, in Guatemala and beyond.